Relación entre la automedicación y el estadio anatomo-patológico en la evolución de la apendicitis aguda - Castillo Gonzalez, Samuel Alexander (2014)
To determine this relationship between self-medication and pathological stage in the evolution of acute appendicitis in patients admitted to the HBT during 2008-2012. MATERIALS Y METHODS: The design used corresponds to a descriptive, cross-sectional retrospective study. 456 medical records of patients with acute appendicitis of HBT was revised during the period 2008-2012, of which 342 met the inclusion criteria. RESULTS: We found that 62 % of patients were male, with a 1.65:1 male -female relationship; individuals more frequently in acute appendicitis are between 19 and 29 years old. The years with the highest percentage of acute appendicitis were 2011 (31%), 2010 (23%) and 2012 (22%). Remained high during the month of June (11%). The place of occurrence was '' '' Trujillo (27%). 77% of patients are self-medicating. The anatomo - pathological was found more frequently stage was complicated in this perforated with 69.3 %. In relation to self-medication - pathological stage was found that the vast majority of complicated appendages were in patients who are self-medicating. As for the relationship pathological stage and pre -hospital time was determined that the higher pre -hospital time greater is the percentage of complicated appendices. The complication rate during the years 2008 - 2012 was 6 per 100 patients. The fatality rate for the years 2008 - 2012 was 0 deaths per 100 patients. CONCLUSIONS: Complicated, gangrenous and perforated pathological stages are related to a greater extent with self-medication. Self-medication is related to the complication of acute appendicitis. Postoperative complications in patients with acute appendicitis occur at higher rates in patients who self-medicate. There is no relationship between patients' gender and self-medication. Patients who had higher self-medicated pre-hospital time